Dravet syndrome - Incorpora Gemma (BMC, 2009)
Abstract "Dravet syndrome" (DS) previously named severe myoclonic epilepsy of infancy (SMEI), or epilepsy with polymorphic seizures, is a rare disorder characterized by an early, severe, generalized, epileptic encephalopathy. DS is characterized by febrile and afebrile seizures beginning in the 1st year of life followed by different types of seizures (either focal or generalized), which are typically resistant to antiepileptic drugs. A developmental delay from the 2nd to 3rd year of life becomes evident, together with motor disturbances and personality disorders. Beside the classic syndrome, there are milder cases which have been called severe myoclonic epilepsy borderline (SMEB). DS is caused by a mutation in the neuronal sodium channel gene, SCN1A , that is also mutated in generalized epilepsy with FS+ (GEFS+).